PELAYANAN PUBLIK DALAM TRANFORMASI “SAKIP” PADA PEMERINTAH KECAMATAN BANGOREJO - Sutikno, Sugeng; Priyanto, Hary; Pahlevi Hentika , Niko (JURNAL KATARSIS, 2025)
This research raises the main issue regarding the suboptimal implementation of the Government Agency Performance Accountability System (SAKIP) within the Bangorejo Subdistrict Government.The performance of government officials in the area is still considered suboptimal in carrying out public service functions to the community.The evaluation results from the Banyuwangi District Inspectorate indicate that the biggest obstacle lies in the understanding and skills of human resources in consistently implementing SAKIP.In addition, the existence of vacant positions within the organizational structure also serves as an impediment to achieving optimal service performance.The main objective of this research is to describe the implementation of SAKIP and its direct impact on the quality of public services provided.The urgency of this research lies in the importance of providing data-driven and solution-oriented policy recommendations to promote more accountable governance in Bangorejo District.The method used in this research is a qualitative descriptive approach that allows for an in-depth exploration of the phenomenon being studied.Data collection techniques were carried out through in-depth interviews with key informants and direct field observations.Data is analyzed through the stages of reduction, presentation, and conclusion drawing.The results show that the aspects of organization, interpretation, and application greatly influence the effectiveness of SAKIP.The conclusion of the research emphasizes the need for improving human resource capacity and organizational structure.